(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Jatyadi thailam is traditional formulation widely used to treat chronic wounds. Reverse pharmacology approach is employed to study the mode of action of two traditional formulations of thailam-AFI Jatyadi thailam (JT-AFI) and Jatyadi thailam-Yogagrantha (JT-YG) against radicals DPPH, ABTS, Nitric oxide, hydroxyl, and superoxide radicals and inflammatory mediators in vitro, namely Nitric oxide, 5-Lipoxygenase and cyclooxygenase-1, and cyclooxygenase-2. Both formulations of Jatyadi thailam rendered dose-dependent inhibition of free radicals and demonstrated their reduction potential.. The free radical formation is inextricably associated to the inflammatory process. The formulations significantly reduced nitrite at its highest concentration in LPS-induced RAW264.7 macrophage cells. The formulations also unveiled subsequent dose-dependent inhibition of 5-Lipoxygenase, Cyclooxygenase-1, and Cyclooxygenase-2 enzymes. JT-AFI proved to be a selective inhibitor for COX-2 with a COX-1/COX-2 ratio of 1.924, while JT-YG was COX-1 selective (0.794). The study's outcome indicated that JT-AFI exhibited superior antioxidant and anti-inflammatory activities than JT-YG. The current investigation could shed insights on the scientific validation of the use of Jatyadi thailam in chronic wound management.